FENOMENA-FENOMENA ALAM DALAM PERSEPEKTIF SAINS MODERN - FARIDA, NUR; MUNTAHA, DARUL (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2019)
Man was created by God with a high mind to have the ability to manage the universe and its contents for human needs and benefits, with science that can be obtained by humans with their minds. This is what is called science, engineering and technology. The Qur'an explains the word of God, that the universe or the world was created by Allah with a specific purpose. The Qur'an is a guideline for manuia, guidance and mercy for those who believe this proves that many astronomers produce counted days and days, months and years of the verses of the Qur'an used as a reflection and sign about the existence, majesty, greatness of the unity of the Creator of nature, namely Allah SWT. The Qur'an does not teach people to look for worlds only, nor does it teach them to seek after death by forgetting the world. As for the statements of the Qur'an regarding the creation of the pseudo universe, it shows that there is a plan in it. So that people who think will know, that the creation of the universe must contain a specific purpose and purpose. To understand science, humans are required to use their minds, learn, and understand them. In education, science is the most important and essential thing. Education is a human effort to foster personality in accordance with human nature. On this basis, religion is needed by humans as the nature given by God to humans is the rules that consist of beliefs and works that are linked to sacred conditions.